2019
DOI: 10.1038/s41467-019-09981-6
|View full text |Cite
|
Sign up to set email alerts
|

PFA ependymoma-associated protein EZHIP inhibits PRC2 activity through a H3 K27M-like mechanism

Abstract: Posterior fossa type A (PFA) ependymomas exhibit very low H3K27 methylation and express high levels of EZHIP (Enhancer of Zeste Homologs Inhibitory Protein, also termed CXORF67). Here we find that a conserved sequence in EZHIP is necessary and sufficient to inhibit PRC2 catalytic activity in vitro and in vivo. EZHIP directly contacts the active site of the EZH2 subunit in a mechanism similar to the H3 K27M oncohistone. Furthermore, expression of H3 K27M or EZHIP in cells promotes similar chromatin profiles: lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
166
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 61 publications
1
166
0
2
Order By: Relevance
“…7). Given the unique role of H3K27me3 in gene repression and disease pathogenesis (Wigle et al 2011;Yap et al 2011;Lee et al 2018b;Oksuz et al 2018;Hübner et al 2019;Jain et al 2019), it is telling that automethylation of PRC2 mainly participates in the rate-limiting process of attaining the highest H3K27 methylation state (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…7). Given the unique role of H3K27me3 in gene repression and disease pathogenesis (Wigle et al 2011;Yap et al 2011;Lee et al 2018b;Oksuz et al 2018;Hübner et al 2019;Jain et al 2019), it is telling that automethylation of PRC2 mainly participates in the rate-limiting process of attaining the highest H3K27 methylation state (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…EZHIP bears a methionine residue, similar to the H3 lysine-to-methionine (K27M) mutation, that is critical for mediating global H3K27me3 reduction [6,7,13]. The genomic distribution of H3K27me3 in H3K27M DIPGS and PFAs show remarkable similarities suggesting that these two tumors may be epigenetically related and share similar pathogenic mechanisms [2,7]. Indeed, in support of this hypothesis,~4% of PFAs demonstrate H3K27M mutations that are mutually exclusive from EZHIP mutations [11].…”
mentioning
confidence: 96%
“…Additionally, three independent groups have demonstrated that EZHIP mimics the H3K27M "oncohistone" to cause global H3K27me3 reduction. EZHIP bears a methionine residue, similar to the H3 lysine-to-methionine (K27M) mutation, that is critical for mediating global H3K27me3 reduction [6,7,13]. The genomic distribution of H3K27me3 in H3K27M DIPGS and PFAs show remarkable similarities suggesting that these two tumors may be epigenetically related and share similar pathogenic mechanisms [2,7].…”
mentioning
confidence: 99%
“…CXORF67, now termed EZH1/2 Inhibitory Protein (EZHIP), is normally expressed predominantly in gonads, where it limits PRC2 enzymatic activity . EZHIP contains an amino acid sequence with similarities to the K27M mutant histone H3 tail and also places a methionine in the lysine‐binding pocket of EZH2, resulting in even more potent inhibition of PRC2 . In agreement with this proposed overlap of mechanism, H3K27M mutations are found with low frequency in PFA ependymomas and are always mutually exclusive with high expression of EZHIP .…”
Section: H3k27m Exerts a Dominant Negative Effect On H3k27me3 Throughmentioning
confidence: 88%